Pemanfaatan Media Youtube dalam Meningkatkan Motivasi Belajar Bahasa Indonesia di Paud Aster 36 - Agustini, Setyorini Dwi; Yuliana, Siti; Hamliyah, Hamliyah (LPPM Institut Pendidikan Nusantara Global, 2024)
Early childhood education (ECED) is a critical phase in child development that encompasses cognitive, social and emotional aspects. In today's digital era, social media such as YouTube offers great potential to enrich early childhood learning experiences. This research aims to explore how the utilization of YouTube can increase children's Indonesian language learning motivation at PAUD ASTER 36. The research method used is descriptive qualitative, which allows for an in-depth understanding of the use of YouTube in the context of early childhood education and its impact on Indonesian language learning motivation. Data collection techniques included in-depth interviews and observations with parents, educators and children. The results show that educational videos on YouTube that are engaging and interactive, such as animations and educational songs, increase ECED children's interest and engagement in Indonesian language learning. However, it is important to choose quality content and manage the duration of screen time wisely. This study concludes that YouTube can be an effective learning tool if used in the right way, including integration with traditional learning methods and close monitoring of screen time.